Handover procedure between femtocell and macrocell analysis based on hysteresis margin and time-to-trigger in LTE network / Zain Azwan Zain Azni - Zain Azni, Zain Azwan (2013)
In the purpose of offering extensively higher data rates, higher systems throughput, and lower latency the 3 GPP LTE system has premeditate. The goals for handover are to keep the continuity of the communication, enhance the capacity and the quality of service. There are problems that occur during the handover process between macrocell and femtocell. Handover procedures for existing networks are needed to support the macrocell/femtocell integrated network. In a large number of femtocells, there are too many prehandover and unnecessary handover processes frequently occur. Call termination due to handover where it happens when the mobile moves from one serving cell to another cell. High number of switching load will bring to ping-pong effect. The objective of this research is to analyze the result of handover performance between femtocell and macrocell. The related scope of work is simulating and analyzing the handover parameters which are Hysteresis Margin (HM) and Tiffie-fb-Trigger (TTT) incorporating with threshold level for the handover from femtocell to macrocell. The method used in this paper is by deploying the hierarchical macro/femtoMAcell. The existence of femtocell will improve the handover performance because femtocell helps offloading the macrocell. The result shows that the deployment of femtocell has increase the handover performance.